Prison Reform in England: An Overview - Carlie, Michael K. (International journal of offender therapy and comparative criminology, 1993)
Using data gathered in interviews with members of the British penal reform lobby and the Prison Service, observations in Her Majesty's Prisons, and a review of the literature, the author introduces the reader to the British penal reform movement. While reforms at the preand post-incarcerative stages are reviewed, the emphasis of the research is on identifying the need for and kinds of incarcerative reform. The process of penal reform in England is outlined and barriers to change are identified